Together The Science of Social Psychology - Biswas-Diener, Robert; Diener, Ed (Open textbook library., 2016)
This textbook presents core concepts common to introductory social psychology courses. The 8 units include 27 modules covering key social psych topics such as research methods, group processes, social influence, and relationships. This book can be modified: feel free to add or remove modules to better suit your specific needs. Each module in this book is accompanied by instructor's manual, PowerPoint presentation, test items, adaptive student quiz, and reading anticipation guide.Please note that the publisher requires you to login to access and download the textbooks.